Suggested application of HER2+ breast tumor phenotype for germline TP53 variant classification within ACMG/AMP guidelines - Fortuno, Cristina (Hum Mutat, 2020)
Early-onset breast cancer is the most common malignancy in women with Li-Fraumeni syndrome, caused by germline TP53 pathogenic variants. It has repeatedly been suggested that breast tumors from TP53 carriers are more likely to be HER2+ than those of non-carriers, but this information has not been incorporated into variant interpretation models for TP53. Breast tumor pathology is already being used quantitatively for assessing pathogenicity of germline variants in other genes, and it has been suggested that this type of evidence can be incorporated into current ACMG/AMP guidelines for germline variant classification. Here, by reviewing published data and using internal datasets separated by different age-groups, we investigated if breast tumor HER2+ status has utility as a predictor of TP53 germline variant pathogenicity, considering age at diagnosis. Overall, our results showed that the identification of HER2+ breast tumors diagnosed before the age of 40 can be conservatively incorporated into the current TP53-specific ACMG/AMP PP4 criterion, following a point system detailed in this manuscript. Further larger studies will be needed to re-assess the value of HER2+ breast tumors diagnosed at a later age.